1, 2, 3, 9b-Tetrahydro-5H-imidazo[2, 1-a]isoindol-5-ones as a new class of respiratory syncytial virus (RSV) fusion inhibitors. Part 2: Identification of BTA9881 as a preclinical candidate. Issue 4 (15th February 2015) - Bond, Silas; Draffan, Alistair G.; Fenner, Jennifer E.; Lambert, John; Lim, Chin Yu; Lin, Bo; Luttick, Angela; Mitchell, Jeffrey P.; Morton, Craig J.; Nearn, Roland H.; Sanford, Vanessa; Anderson, Kelly H.; et al.
Graphical abstract